Game Analysis of Scoring Strokes in Men's Singles and Men's Doubles Badminton (JTIKOR (Jurnal Terapan Ilmu Keolahragaan), 2024)
This study aims to analyze the effectiveness of various strokes in scoring points in men’s singles and doubles badminton, as well as to determine the contribution of each stroke to overall scoring performance. Badminton requires a blend of technical skill, tactical awareness, and physical endurance, with notable differences in strategy and stroke selection between singles and doubles formats. A descriptive comparative research design was employed, using game analysis as the primary method. The study involved eight randomly selected active players from a population of 30 athletes in the UPI Badminton Club. Data were collected through simulated matches consisting of eight sets, with stroke occurrences recorded using the sign system method. Statistical analyses were conducted using the Independent Samples T-Test or the Mann-Whitney U Test, depending on data distribution. The results indicate that Smash Shot, Drive Shot, and Cut Drop Shot showed statistically significant differences in effectiveness between singles and doubles formats (p 0.05). In contrast, Drop Shot, Net Shot, Clear Shot, Jump Smash Shot, Cut Smash Shot, and Net Kill Shot did not present significant differences (p 0.05). These findings suggest the importance of tailoring training strategies based on the specific demands of singles and doubles play. Singles players are advised to prioritize strokes that emphasize control and endurance, while doubles players should focus on rapid, well-coordinated shot execution. This study offers practical insights for coaches and athletes aiming to optimize performance through format-specific training.